Interaction of cationic antimicrobial peptides from Australian frogs with lipid membranes. Issue 3 (14th March 2018) - Zhu, Shiying; Sani, Marc‐Antoine; Separovic, Frances
Abstract: Cationic antimicrobial peptides (AMPs) from Australian frogs have been extensively studied as alternatives to traditional antibiotics. Solid‐state NMR is used to characterize their effect on lipid bilayers, which are the primary target, but correlation with in vivo situations is tentative in view of the complex effects of changes in sample conditions (such as pH, temperature, lipid composition or peptide concentration). We have used 31 P and 2 H solid‐state NMR and a range of biophysical techniques to study the impact of the AMPs, maculatin 1.1, caerin 1.1, aurein 1.2, kalata B1, and Chex‐Arg20, on membranes that mimic those of E. coli and S. aureus bacteria and red blood cell membranes. Overall, the length of AMPs affects peptide‐membrane interaction but also their conformations are important. While lipid composition plays a critical role in modulating AMP structure and function, electrostatic interactions are not sufficient to explain their specific activity and interactions with other membrane components need to be considered. Although in an early stage of development, in‐cell NMR of labelled peptides in live bacteria, rather than model membrane studies, may provide new insights into bactericidal mechanisms of AMPs. Abstract :